2020
DOI: 10.1016/j.eneco.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Mild explosivity in recent crude oil prices

Abstract: This paper provides an analysis of oil prices during and in the aftermath of the Global Financial Crisis, concentrating on the 2007-08 price spike and the 2014-16 price decline. The mildly explosive/multiple bubbles testing strategy by Phillips, Shi and Yu (2015, International Economic Review 56(4), 1043-1133) is used to test for price departures from an underlying stochastic trend and to assess whether any such departures can be explained by fundamentals or other proxy variables. The test dates two significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 85 publications
(112 reference statements)
2
17
0
1
Order By: Relevance
“…They suggest that a speculative bubble was present in the pre-2008 burst. Figuerola-Ferretti et al [54] suggest two bubbles in Brent and WTI prices, one positive prior the 2008 crisis and a negative one between 2014 and 2016. Global economic activity can well explain the first one, but speculation cannot.…”
Section: Literature Reviewmentioning
confidence: 98%
“…They suggest that a speculative bubble was present in the pre-2008 burst. Figuerola-Ferretti et al [54] suggest two bubbles in Brent and WTI prices, one positive prior the 2008 crisis and a negative one between 2014 and 2016. Global economic activity can well explain the first one, but speculation cannot.…”
Section: Literature Reviewmentioning
confidence: 98%
“…One of the most important recent contributions is the approach by Phillips, Wu & Yu (2011), which has been very influential for numerous empirical studies as it takes the critique of Evans (1991) that conventional unit root and cointegration tests have little power for periodically collapsing bubbles, into account. Given this approach, right-tailed unit root testing has been used in different segments of global financial markets, ranging from equity markets to housing markets to commodity futures such as crude oil markets (see, for example, Homm & Breitung, 2012, Kivedal, 2013, Engsted, Hviid & Pedersen, 2016, Pavlidis, Paya & Peel, 2017, Figuerola-Ferretti, McCrorie & Paraskevopoulos, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…ey found statistical evidence of the presence of a short price bubble between March and July 2008. Tsvetanov et al [17], Figuerola-Ferretti et al [18], and Caspi et al [39] employed the GSADF test of PSY using different samples and reported multiple bubble episodes of oil price explosivity during the period under examination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As shown in Tao et al [25], when σ 2 � 0, model ( 21) collapses to a simple autoregression with a constant coefficient. It explains why a popular way to look for bubbles is to test ϕ � 0 against ϕ > 0 via standard or recursive right-tailed unit root tests [15][16][17][18]27]. For the purpose of the present paper, we only examine three price behavior features that are divided into three categories:…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation